2018
DOI: 10.1101/438390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analyses of Neanderthal introgression suggest that Levantine and southern Arabian populations have a shared population history

Abstract: ObjectivesModern humans are thought to have interbred with Neanderthals in the Near East soon after modern humans dispersed out of Africa. This introgression event likely took place in either the Levant or southern Arabian depending on which dispersal route out of Africa was followed. In this study, we compare Neanderthal introgression in contemporary Levantine and southern Arabian populations to investigate Neanderthal introgression and to study Near Eastern population history.Materials and MethodsWe analyzed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Instead, our results reveal that the current geographical heterogeneity of NE ancestry is due to dynamics that occurred during the more recent Neolithic expansion ~10,000 BP. The early FA populations, which are probably related to the previously identified basal Eurasian lineage 18,19,49 , admixed with HG, leading to a progressive increase in HG ancestry and consequently NE ancestry in the expanding FA populations. The partial replacement of HGs by FAs 31,32 thus contributed to reducing the level of NE ancestry in western Eurasia more than in eastern Eurasia.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Instead, our results reveal that the current geographical heterogeneity of NE ancestry is due to dynamics that occurred during the more recent Neolithic expansion ~10,000 BP. The early FA populations, which are probably related to the previously identified basal Eurasian lineage 18,19,49 , admixed with HG, leading to a progressive increase in HG ancestry and consequently NE ancestry in the expanding FA populations. The partial replacement of HGs by FAs 31,32 thus contributed to reducing the level of NE ancestry in western Eurasia more than in eastern Eurasia.…”
Section: Discussionmentioning
confidence: 87%
“…5). Note that it was recently found that modern Levantine and southern Arabian populations still have lower NE ancestry than northern Eurasian populations 49 .…”
Section: Spatial Gradients In European Farmers and Hunter-gatherersmentioning
confidence: 99%